2010
DOI: 10.1177/0961203310367504
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in primary Sjögren's syndrome: a case-control study in 624 patients

Abstract: We evaluated the prevalence and clinical significance of cardiovascular risk factors in a large series of patients with primary Sjögren's syndrome (SS), focusing on the possible association with clinical and immunological SS features, the therapies administered, and the impact on cardiovascular disease. The study cohort included 312 patients fulfilling the 2002 classification criteria for primary SS, consecutively evaluated and followed in our department between 1984 and 2009. The control group consisted of 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 37 publications
10
62
4
Order By: Relevance
“…Supporting this observation, in a cohort of young women with primary SS who were not receiving corticosteroids or immunosuppressive agents, the frequency of increased CIMT defined as a mean CIMT Ͼ0.90 mm was approximately half (9). In contrast, Perez-de-Lis et al found that primary SS patients with Ն3 CV risk factors took corticosteroids more frequently than those without CV risk factors (5).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Supporting this observation, in a cohort of young women with primary SS who were not receiving corticosteroids or immunosuppressive agents, the frequency of increased CIMT defined as a mean CIMT Ͼ0.90 mm was approximately half (9). In contrast, Perez-de-Lis et al found that primary SS patients with Ն3 CV risk factors took corticosteroids more frequently than those without CV risk factors (5).…”
Section: Discussionmentioning
confidence: 80%
“…Primary SS shares several pathophysiologic characteristics with SLE, such as systemic inflammation and immunologic disturbances that indicate the presence of circulating autoantibodies (e.g., rheumatoid factor [RF] and antinuclear and anti-SSA/SSB antibodies). In addition, an increase in traditional CV risk factors such as hypertension and dyslipidemia has also been observed in primary SS (5,6). In this setting, it is conceivable that patients with primary SS may also have an increased CV risk.…”
Section: Introductionmentioning
confidence: 99%
“…The results are summarized in Tables II, III and IV. DISCUSSION Convincing evidence demonstrates that connective tissue diseases· such as rheumatoid arthritis, systemic lupus: erythematosus, antiphospholipid syndrome and others, are associated with increased prevalence of atherosclerosis, cardiovascular risk and increased mortality (1-9, 18, 19); chronic inflammation, immunologic alterations and the need for immunosuppressive treatment (steroids) greatly favor the development of early atherosclerosis (20). On the other hand, diabetes mellitus and hypertriglyceridaemia have been detected to be the most important cardiovascular risk factors in pSS, especially when the patients have been massively treated with corticosteroids (21). However, pSS rarely shows a significant systemic chronic inflammation and it does not often need treatments that may be vessel-injuring (22).…”
Section: Discussionmentioning
confidence: 99%
“…Disease duration and several clinical and immunological features, including joint involvement, parotid swelling, Raynaud's phenomenon, leucopenia and anti-SSA/Ro and anti-SSB/La antibodies, seem to contribute to subclinical ATS damage in these patients [12][13][14][15][16]. By contrast, the prevalence and the role of traditional CV disease risk factors in the induction of precocious ATS have not been extensively investigated [17,18]. In addition, the risk of clinically manifested major CV events and long-term CV outcome in patients with pSS remain unclear.…”
Section: Introductionmentioning
confidence: 99%